A Preliminary Qualitative Analysis on the Feasibility of Using Gaming Technology in Caregiver Assessment. Issue 3 (3rd July 2017) - Hughes, Jennifer C.; Banerjee, Tanvi; Goodman, Garrett; Lawhorne, Larry
ABSTRACT: This exploratory qualitative study examined the feasibility of utilizing gaming technology that will ultimately assess task performance and stress among caregivers of dementia patients. The long-term goal is to use this unobtrusive application (app) to detect caregiver burnout for the purposes of early intervention. This preliminary study examined participant interface with a specific gaming technology called CAST (Caregiver Assessment Using Serious Gaming Technology). Ten dementia caregivers participated. Participants attended a demonstration and then interacted with a preliminary version of the CAST tablet application. Social work researchers interviewed participants using open-ended questions to gauge interest, technology skill level, and comfort with the app. Participants expressed interest and identified potential ways to further develop the system in order to increase ease of use, decrease time commitment, and improve suitability for daily use. The provided feedback will be used to refine the user interface of the application, which will then be used to monitor caregivers' stress in future development.